(untitled) (EU and comparative law issues and challenges series (ECLIC), 2021)
Competition law as one of the foundations of a market economy whose main purpose is to ensure an equal position of entrepreneurs in the market, regardless of the size, market power and other features of the implied system of state aid both at central and local and regional level. The aim and purpose of this research is a clear and tentative way of pointing out the importance of competition in relation to coronavirus. In order to achieve this goal, the paper seeks to provide scientifically based answers to a number of current issues, starting from detention from the definitions of competition and coronavirus. In addition to the above, it is necessary to consider how this disease affected entrepreneurship, which had positive and negative consequences. In addition, it is important to note that it has left a significant impact on our mental health. The main results of the research point to the fact that the coronavirus as a global, economic and health crisis suddenly caught us all overnight and as such changed our lives. In addition to greatly affecting the economy, there is also a blow to the company. In case of suspicion of infection, the obligation to call a doctor, ie a territorially competent epidemiologist, and the obligation to go to an outpatient clinic are determined as a preventive measure. In this paper, qualitative research in correlation with quantitative research was used. Starting from the fact that quantitative research is based on the description of individual conditions, ie the establishment of cause-and-effect relationships, the paper in a representative way seeks to simplify the concept of competition as the driving force of a market economy that entails many benefits consumer choice, innovation. In addition, considering the coronavirus from a quantitative point of view, it is manifested in how the coronavirus as a new strain of virus, discovered in humans, ’stirred’ the whole world as such forced people to care about their health and the health of our loved ones. Also, an obligation to adhere to epidemiological measures to prevent the spread of coronavirus infection has been introduced. Qualitative research, as a term used to describe research that focuses on the way individuals and groups view and understand the world, also has a significant impact on this work, primarily because it considers how the pandemic affected the health of people interacting with each other.